Adults’ Versus Elders’ Perceived Understanding of The Endangered Lexicons of The Kepus Pungsed Ritual in Menyali Village - Ni Made Manda Risva Pebbyanti; I Gede Budasi; I Ketut Trika Adi Ana (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2026)
The Kepus Pungsed ritual, a Balinese Hindu life-cycle ceremony performed in Menyali Village, embodies a set of culturally and spiritually significant lexicons that function as a medium for transmitting traditional knowledge. This study aims to (1) describe the level of perceived understanding of the Kepus Pungsed ritual lexicons among adults, (2) describe the level of perceived understanding among elders, and (3) determine whether there is a significant difference between the two groups. This research employed a quantitative comparative cross-sectional design. Data were collected through a structured questionnaire consisting of 36 ritual lexicons administered to 100 respondents, comprising 50 adults and 50 elders in Menyali Village. The data were analyzed using descriptive statistics and inferential analysis through the Mann–Whitney U test. The findings reveal a substantial generational gap in perceived understanding. Adults demonstrate a low level of perceived understanding, with 76% categorized as very low and 24% as low. In contrast, elders show a high level of perceived understanding, with 72% categorized as very high and 28% as high. The inferential analysis confirms that there is a statistically significant difference between adults and elders in their perceived understanding of the ritual lexicons. These findings indicate that the lexicons of the Kepus Pungsed ritual are in a vulnerable state due to the decline in comprehension among the younger adult generation. This study highlights the urgency of strengthening intergenerational transmission and suggests the integration of cultural and linguistic elements, particularly through English language education, to support the preservation and revitalization of endangered ritual lexicons.